A Phenolic Derivative and Two Diacetylenes from Symphyotrichum subulatum - Lee, Kai; Shen, Chien-Chang; Lin, Chwan-Fwu; Li, Shyh-Yuan; Huang, Yu-Ling (Planta Medica, 2012)
A pytochemical study on the constituents of the roots of Symphyotrichum subulatum led to the isolation of three new compounds including two diacetylenes, asterynes A (1) and B (2), and (E)-4-(3-acetoxyprop-1-enyl)-2-methoxyphenyl (S)-2-methylbutanoate (3) along with twelve known compounds. Their structures were elucidated with spectroscopic analyses. Compound 3 showed anti-inflammatory activity on LPS-induced NO production with an EC50 value of 15.0 µM.
Keywords: Symphyotrichum subulatum; Asteraceae; asteryne A; asteryne B; (E)-4-(3-acetoxyprop-1-enyl)-2-methoxyphenyl (S)-2-methylbutanoate; anti-inflammatory